Time of Lactation and Maternal Fucosyltransferase Genetic Polymorphisms Determine the Variability in Human Milk Oligosaccharides - Lefebvre, Gregory; Shevlyakova, Maya; Charpagne, Aline; Marquis, Julien; Vogel, Mandy; Kirsten, Toralf; Kiess, Wieland; Austin, Sean; Sprenger, Norbert; Binia, Aristea (Frontiers in Nutrition, 2020)
Rationale: Human milk oligosaccharides (HMOs) vary among mothers and genetic factors contribute to this variability. We assessed changes in HMO concentrations during the first year of lactation and the relationship with FUT2 Secretor group and FUT3 Lewis group defining genetic polymorphisms. Methods: Milk samples were collected from lactating mothers participating in the LIFE Child cohort in Leipzig, Germany. The concentrations of 24 HMOs in milk samples collected at 3 months (N=156), 6 months (N=122) and 12 months (N=28) were measured using liquid chromatography. Concentrations of HMOs were compared at all time-points and were tested for their associations with FUT2 and FUT3 genetic variations by sPLS regression. Results: FUT2 SNP rs601338 was found to predominantly define the Secretor status Se-: 11.8% and it was highly correlated with 2’-fucosyllactose (2’FL, p<0.001) and lacto-N-fucosylpentaose-I (LNFP-I, p<0.001). FUT3 SNPs rs28362459 and rs812936 were found to define Lewis status (Le-: 5.9%) and correlated with lacto-N-fucosylpentaose-II (LNFP-II, p<0.001). A polygenic score predicted the abundance of 2’FL levels within Secretors’ milk (adj.R2=0.58, p<0.001). Mean concentrations of most of the individual HMOs, as well as the sums of the measured HMOs, the fucosylated HMOs, and the neutral HMOs were lower at 6 and 12 months compared to 3 months (p<0.001). Conclusions: Secretor and Lewis status defined by specific FUT2 and FUT3 SNPs are confirmed to be good proxies for specific individual HMOs and milk group variabilities. The polygenic score developed here is an opportunity for clinicians to predict 2’FL levels in milk of future mothers. These results show opportunities to strengthen our understanding of factors controlling FUT2 and FUT3 functionality, the temporal changes and variability of HMO composition during lactation and eventually their significance for infant development.